The Preparation of pH Indicator Paper from Bagasse Fiber with Anthocyanin Extract from Butterfly Pea Flower, Purple Cabbage and Lxora Coccinea for an Acid-Base Soil Monitoring Application - Theamdee, Pawinee; Chawpaina, Pakaporn; Polthana, Siraprapha (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2023)
The objective of this research was to prepare pH indicator paper from bagasse fiber with anthocyanin extract from butterfly pea flower, purple cabbage and Ixora coccinea to acid-base soil monitoring. The handmade paper was prepared by treating bagasse with 20 %w/v sodium hydroxide at 90 - 95 degrees Celsius for 3 hours, and pulp was bleached with 25 %v/v hydrogen peroxide for 2 hours. Afterward, different weights, 40, 50, 60, and 70 grams, of bagasse fiber were separately prepared into paper by molding in rectangular shape trays and subsequently dried at ambient conditions for 2 days After drying, the physical and mechanical properties of paper from bagasse; water absorption, compression test, puncture strength, and degradation were evaluated. As a result, the appropriate weight was 60 grams of bagasse fiber. The paper from bagasse fiber (60 grams) was dried at 45 degrees Celsius for 30 minutes before loading the indicator. During loading, 50 microlite anthocyanin extracts from butterfly pea flower, purple cabbage and Ixora coccinea were deposited on the paper. After loading, the paper was dried at the ambient condition for 30 minutes. The efficiency of the indicator paper from bagasse fiber with anthocyanin extract was studied in different buffer solutions of pH ranging 1-14 and tested for acid-base soil monitoring. The indicator paper from bagasse fiber with anthocyanin extract showed a clear response to pH variation. The degradation study of the paper from the bagasse (60 grams) sample was buried under the ground (8 - 10 cm depth) for 8 months at ambient temperature (28±2 degrees Celsius), which was degraded by 61.12 Percentage. Therefore, which could be used as a green route monitoring for acid-base soil using low-cost and sensitive pH indicators. In addition, this made of natural material is biodegradable which can reduce the amount of waste.